An improved asynchronous energy-saving mechanism for IEEE 802.15.5-based networks - Li-yong Yuan; Fei-long Lin; Jun-ke Lv (International Journal of Distributed Sensor Networks)
IEEE 802.15.5 standard introduces the mesh routing which improves reliability and robustness of routing in wireless sensor network since there are multiple routes from source node to destination node. To achieve energy efficiency for a long network lifetime, the asynchronous energy saving is proposed in IEEE 802.15.5, which includes the receiver-initiated unicast mechanism and the sender-initiated broadcast mechanism. In this article, an improved asynchronous energy saving named semi-synchronous energy saving is proposed to deal with the energy inefficiency from idle listening existing in asynchronous energy saving. In semi-synchronous energy saving, every node maintains the wake/sleep schedule information of nodes in its two-hop neighborhood and uses this information to calculate the wake-up time of an interested neighbor that the data will be sent to, which reduces idle listening time in both unicast and broadcast mechanisms. A low delay routing mechanism is also proposed based on the wake/sleep schedule information of neighbors. Furthermore, the optimal guard time to guarantee receiving the wake-up notification from neighbor in the presence of clock drift is investigated for saving energy. The performance analysis and simulation evaluation show that semi-synchronous energy saving saves more than 80% of energy with less than 30% memory cost compared to asynchronous energy saving, and it also improves the time of completing broadcast and the end-to-end delay.